Elotuzumab in multiple myeloma: a single centre experience - Galli, Monica; Stefanoni, Paola; Paris, Laura; Pavoni, Chiara; Delaini, Federica; Rambaldi, Alessandro (European Journal of Oncology and Environmental Health, 2018)
Background and aims of the work: Elotuzumab is a first-in-class immunostimulatory monoclonal antibody approved in Italy in April 2017 for use in combination with lenalidomide and dexamethasone (ELd) for relapsed/refractory multiple myeloma (MM). We present our single Centre experience with ELd in patients with MM, focusing on the determinants driving the choice of the most appropriate second-line treatment. Methods: We performed a retrospective analysis of patients experiencing a first relapse in the Hematology and Bone Marrow Transplant Unit of the Papa Giovanni XXIII hospital in Bergamo, Italy between April and December of 2017. Results: We tended to administer ELd treatment to young and fit patients with non-aggressive relapsed/refractory MM. In general, ELd was well tolerated. We present details of 2 illustrative cases. Conclusions: The immunostimulatory effects and favorable clinical toxicity profile of elotuzumab make it an ideal drug against MM. Ongoing clinical trials will elucidate its most appropriate placement and its best combination partners to improve disease control and, therefore, the duration and quality of life.